Beliefs, knowledge, actions of nursing techniques in breastfeeding in pain management in immunization - Isadora Trinquinato Rosa; Lisabelle Mariano Rossato; Danila Maria Batista Guedes; Vanessa Dias Fogaça; Flávia Domingues; Lucía Silva (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: Understand the beliefs, knowledge, and actions of nursing technicians on breastfeeding as a form of non-pharmacological intervention to relieve pain in newborns and infants during immunization. Methods: Qualitative study carried out through semi-structured interviews with nine nursing technicians from three Basic Health Units in a city in the state of São Paulo. The theoretical approach of the Belief Model and the methodological framework of Thematic Analysis supported this study. Results: Three themes originated: Beliefs, Knowledge, and Actions of nursing technicians. Final considerations: Despite knowledge about the benefits of breastfeeding as the most effective method for relieving pain in newborns and infants during vaccination, their restrictive beliefs overrode the evidence, leading them to act in ways that discourage or prevent the mother from breastfeed during vaccination. Formal training is recommended to align with current evidence-based practices.